2013
DOI: 10.1590/s0103-507x2013000100013
|View full text |Cite
|
Sign up to set email alerts
|

Doença de Marchiafava-Bignami: uma rara entidade com prognóstico sombrio

Abstract: Marchiafava-Bignami disease is a rare affliction characterized by primary degeneration of the corpus callosum associated with chronic consumption of ethanol. The disease may occasionally occur in patients who are not alcoholics but are chronically malnourished. A complex deficiency of group B vitamins is the main etiopathogenic hypothesis, and many patients improve after the administration of these compounds. However, a good response is not always observed. The definitive diagnosis of Marchiafava-Bignami disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 20 publications
1
34
0
Order By: Relevance
“…The present study describes a patient who had undergone cardiac carcinoma surgery three years previously, and who had received chemotherapy three times; the last chemotherapy session was one-and-a-half years prior to admission. The etiology of the patient’s condition may have been similar to that described in a previous study, in which a metabolic disorder of the myelin in the brain of a patient with no long-term alcohol abuse, which was caused by long-term malnutrition involving protein, folic acid and particularly thiamine deficiency, led to demyelinating changes and MBD ( 9 ). The corpus callosum, which is the largest commissural fiber system within the hemisphere, has a relatively high myelin content, and may often cause the degeneration and necrosis of nerve cells in such patients.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…The present study describes a patient who had undergone cardiac carcinoma surgery three years previously, and who had received chemotherapy three times; the last chemotherapy session was one-and-a-half years prior to admission. The etiology of the patient’s condition may have been similar to that described in a previous study, in which a metabolic disorder of the myelin in the brain of a patient with no long-term alcohol abuse, which was caused by long-term malnutrition involving protein, folic acid and particularly thiamine deficiency, led to demyelinating changes and MBD ( 9 ). The corpus callosum, which is the largest commissural fiber system within the hemisphere, has a relatively high myelin content, and may often cause the degeneration and necrosis of nerve cells in such patients.…”
Section: Discussionsupporting
confidence: 67%
“…To date, the etiology of MBD is incompletely understood, as it is one of the rare complications of chronic alcoholism ( 1 2 ). It is believed that MBD may be closely associated with chronic alcoholism and/or malnutrition caused by long-term alcohol abuse; however, MBD can also occur in patients who have no history of alcohol abuse ( 9 11 ). The main hypothesis for MBD pathogenesis is that the condition may be associated with malnutrition or vitamin B deficiency ( 9 ), although it is believed that MBD may have other etiologies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 1 , 2 ] Deficiency of group B vitamins might be the etiology of MBD; it is reported that many patients recover after treatment with B vitamins; however, others do not recover. [ 3 ]…”
Section: Introductionmentioning
confidence: 99%